2015
DOI: 10.1038/pcan.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prospects of long noncoding RNAs as novel biomarkers and therapeutic targets in prostate cancer

Abstract: lncRNA expression is altered in cancer. Aberrant regulation promotes tumor formation, progression and metastasis. lncRNAs can use as tumor markers for PCa and may be attractive novel therapeutic targets for the diagnosis and treatment of PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 52 publications
0
66
0
Order By: Relevance
“…Given their cell-specific expression, lncRNAs have been described as potential biomarkers in various cancers types such as gastric [72], lung [73], prostate [74], and hepatocellular carcinoma [75]. Similarly, several lncRNAs have been identified as potential biomarkers in cells with different OC histotypes, where their expressions levels are altered.…”
Section: Lncrna Signature As a Diagnostic And Prognostic Biomarker Of Ocmentioning
confidence: 99%
“…Given their cell-specific expression, lncRNAs have been described as potential biomarkers in various cancers types such as gastric [72], lung [73], prostate [74], and hepatocellular carcinoma [75]. Similarly, several lncRNAs have been identified as potential biomarkers in cells with different OC histotypes, where their expressions levels are altered.…”
Section: Lncrna Signature As a Diagnostic And Prognostic Biomarker Of Ocmentioning
confidence: 99%
“…Increased levels of blood CTCs are associated with poor survival outcome for patients with prostate cancer (52). Aside from the typically used blood-based PSA test, the urine-based expression test of lncRNA PCA3 may provide information for the early detection of cancer (28,34). Signature analysis of a panel of genes (PCA3, serine peptidase inhibitor Kazal type 1, Golgi phosphoprotein 2 and TMPRSS2:ERG) identified that their presence in urine was demonstrated to be more effective, compared with testing for PCA3 alone, for the early detection of cancer (46).…”
Section: Non-invasive Genetic Biomarker Testmentioning
confidence: 99%
“…Overexpression of prostate cancer associated transcript 1 (PCAT1), another lncRNA, has been identified in a subset of high-grade localized (GS, ≥7) and metastatic tumors (Table I) (27,28). PCAT1 functions to promote cancer cell proliferation through mediating the upregulation of c-Myc and the repression of breast cancer 2, early onset (BRCA2) (35,36).…”
Section: Genetic Biomarkers For Risk Stratification Of Aggressive Cancermentioning
confidence: 99%
See 2 more Smart Citations